2014
DOI: 10.2340/16501977-1865
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the impact of stroke between 3 and 12 months post-stroke, assessed with the Stroke Impact Scale

Abstract: Objective: To examine data collected using the Stroke Impact Scale 3.0 (SIS) at 3 and 12 months post-stroke, and to explore any clinically meaningful changes in everyday life in relation to age, gender and stroke severity. Design: Prospective longitudinal study. Methods: A total of 204 persons were assessed using the SIS at 3 and 12 months after onset of stroke. Changes in domain scores were calculated over time and in relation to age, gender and stroke severity. Results: The Strength, Hand Function and Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
76
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 26 publications
9
76
2
Order By: Relevance
“…A recent study 22 found that almost 50% of their study population had a meaningful positive or negative change within the SIS Participation domain between 3 and 12 months, demonstrating that this domain is sensitive to the impact of stroke over time. The ranges of the participation scores were wide at all time-points, and this could not be explained by stroke severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study 22 found that almost 50% of their study population had a meaningful positive or negative change within the SIS Participation domain between 3 and 12 months, demonstrating that this domain is sensitive to the impact of stroke over time. The ranges of the participation scores were wide at all time-points, and this could not be explained by stroke severity.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 It is also important that persons with stroke feel that their perceptions are important for the research field. 3,21,22 The aim of this study was to investigate perceptions of participation and how this related to background characteristics and self-assessed rehabilitation outcomes, at 1, 6, and 12 months post-stroke. 3,10,[19][20][21] How self-assessed functions associate with perceived participation is not well known, and there is a knowledge gap concerning factors that influences the level of experienced participation over time.…”
Section: Introductionmentioning
confidence: 99%
“…These deficits can also impact on daily living; for example, Guidetti et al . () noted that at 3 and 12 months post stroke, difficulties are experienced in daily activities of living. Issues around sensitive topics such as urinary incontinence, which may continue long after discharge, also impacted on daily functioning (White et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients’ perceptions of their everyday life situation is essential in rehabilitation (Guidetti et al . ) as this can act as a catalyst or barrier to engaging in activities aligned to recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In interaction with environmental factors, all these impairments affect the person's participation (10), and especially mood changes, such as anxiety and depression. Typically, participation is perceived as worst with advancing age and more severe stroke and although no gender difference were found in a recent study (n = 204), age and gender remain 2 variables important to control for (11 Since they invade different aspects of the person's life, mood changes can also restrict participation by affecting self-image and the motivation to get involved in activities. Thus, it can be hypothesized that there is an association between depression and social participation in people who have had a mild stroke.…”
Section: Introductionmentioning
confidence: 99%